CONTEMPORARY ASPECTS OF SPATIAL AND URBAN PLANNING IN THE CANTON OF SARAJEVO - Rahman NURKOVIĆ (European Journal of Geography)
In the paper, contemporary aspects of spatial and urban planning in the Canton of Sarajevo have been analysed. Physical planning and planning of urbanisation in the Canton of Sarajevo make important elements of rational and humane use of space and organisation of economic activities, by adjusting the planning with the technical and technology development, as a phenomenon of the present time, and vital needs of the working people. Area planning in the Canton of Sarajevo is being carried out on the grounds of spatial and development plans of the urban area. Spatial and development plans of the urban area are the social instruments by which a policy of physical planning and urbanisation is implemented. With spatial and development plans of the urban area, a long-term urban development of the Sarajevo Canton, municipalities and the regions is determined.